Problems And Challenges Of Attendance In Medical Students - Khurram, Muhammad (Journal of Rawalpindi Medical College, 2024)
Completing essential training in Medicine, Surgery, Gynecology, and Pediatrics during the final year of Medical College is crucial for individuals aspiring to become doctors. Medical training in Large Group Interactive Sessions and Clinical Clerkships is designed to equip students with knowledge, skills, and experience necessary to practice medicine safely and effectively. Failure to complete essential teaching and training in Medicine, Surgery, Gynecology, and Pediatrics can leave significant gaps in a doctor to be student’s education and preparation for medical practice.1 Without this training, such person will lack necessary clinical skills, experience, and competence to diagnose and treat patients independently. Moreover, they cannot meet standards expected from a qualified doctor which jeopardizes patient safety and well-being. Final year medical students often claim several challenges that affect their attendance in LGIS and clinical rotations, as well as their performance in assessments. When asked for the reasons, they point mainly to; inability to awake, health issues, family obligations, additional educational activities, and religious obligations. Poor time management, lifestyle issues, sleep disorders, and stress contribute to "inability to awake" as reason for deficient attendance.2 Many students have health problems, both physical and mental, which impede their ability to attend lectures and participate in clinical activities effectively. Some have responsibilities towards ill parents, and domestic issues leading to disruption in attending classes regularly and focus on studies. Additional activities include getting clinical electives, and attachments in other national international institutes. As per policy, marks are deduced from continuous internal Assessment (CIA) of Final Year MBBS students who don’t fulfill minimum criteria of attendance for LGIS and Clinical Rotations. Students who miss LGIS and clinical rotations often perform poorly in CIA, affecting their overall grades and readiness for final professional assessments. Failure to meet the required attendance percentage due to various reasons leads to ineligibility to appear in final professional assessments, delaying graduation. Students may opt for grievance and agitation if a large percentage of them have deficient attendance and are barred for appearing in final assessments as per assessment rules. In such cases, the faculty and administrators take actions such as plan remedial assessments, arrange ward or emergency teaching, and or impose fines to allow students with deficient attendance to appear in Professional assessments. As pass percentage in most of the Medical Colleges is ≥90%, most of these students who appear in final assessments will become doctors without issue. What is the answer? Focusing time management strategies, improved sleep hygiene, and mental health support are some of the options that can be used to deal with inability to wake in morning issue. Health issues of the students should be dealt efficiently by Faculty members of concerned specialty. Illnesses requiring short term management can be adjusted according to attendance policy. Students can spend extra hours at concerned rotations unit and take help from duty doctors to gain possible teaching training. For illnesses requiring long term management i.e., absences from blocks such compensatory mechanisms should not be utilized. Student should reattend the LGIS and Clinical Rotations to gain missed competencies. Similarly domestic issues should not be given consideration to waive necessary teaching training. Additional students should be encouraged to plan educational activities, and religious obligations in vacations. The key to improving attendance and quality of education is implementation of rules without fear of consequences as inconsistent attendance and academic performance will lead to inadequate preparation for clinical practice. Possible and judicious flexibility in accommodating personal and health-related challenges can make life easier for both students and administrators. Incorporating and focusing professionalism education into the curriculum emphasizing importance of regular attendance, accountability, and ethical behavior in medical practice can improve students involvement in teaching and training.